2010
DOI: 10.1289/ehp.0901689
|View full text |Cite
|
Sign up to set email alerts
|

Traffic-Related Air Pollution and Incident Type 2 Diabetes: Results from the SALIA Cohort Study

Abstract: BackgroundCross-sectional and ecological studies indicate that air pollution may be a risk factor for type 2 diabetes, but prospective data are lacking.ObjectiveWe examined the association between traffic-related air pollution and incident type 2 diabetes.DesignBetween 1985 and 1994, cross-sectional surveys were performed in the highly industrialized Ruhr district (West Germany); a follow-up investigation was conducted in 2006 using data from the Study on the Influence of Air Pollution on Lung, Inflammation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

28
289
5
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 349 publications
(325 citation statements)
references
References 31 publications
28
289
5
3
Order By: Relevance
“…One article reported two individual cohort studies, and was extracted as two individual studies (14). Thus, ten prospective cohort studies from nine articles were finally included into the meta-analysis (10,11,12,13,14,20,21,22,23). Table 1 shows the main characteristics of those ten cohort studies included in the meta-analysis (Table 1).…”
Section: Literature Search and Study Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…One article reported two individual cohort studies, and was extracted as two individual studies (14). Thus, ten prospective cohort studies from nine articles were finally included into the meta-analysis (10,11,12,13,14,20,21,22,23). Table 1 shows the main characteristics of those ten cohort studies included in the meta-analysis (Table 1).…”
Section: Literature Search and Study Characteristicsmentioning
confidence: 99%
“…Table 1 shows the main characteristics of those ten cohort studies included in the meta-analysis (Table 1). Those ten cohort studies involved a total of 2 371 907 participants and 21 095 incident cases of type 2 diabetes (10,11,12,13,14,20,21,22,23). Among those ten cohort studies, nine studies reported incident new cases of type 2 diabetes (10,11,13,14,20,21,22,23), while the left one reported events of deaths coded as diabetes (12).…”
Section: Literature Search and Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations